2019
DOI: 10.1021/jacs.9b02145
|View full text |Cite
|
Sign up to set email alerts
|

Coordination-Driven Construction of Porphyrin Nanoribbons at a Highly Oriented Pyrolytic Graphite (HOPG)/Liquid Interface

Abstract: Nanostructures were built at the solid/liquid interface by self-assembly and/or coordination bonds. Metalloporphyrins bearing two external coordination sites and long alkyl chains allowed the self-assembly of the compounds on highly oriented pyrolitic graphite. After addition of a metal ion, long transition-metal linked porphyrin nanoribbons were obtained and visualized by scanning tunneling microscopy. In these porphyrin ribbons electronic delocalization is possible through the d orbitals of the connecting me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In a later report, nanoribbons were built from symmetrical porphyrins C31.5a – c or C31.5d – e stabilized by either hydrogen bonding between the enaminoketone fragments or by coordination of nickel(II). 624 …”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“…In a later report, nanoribbons were built from symmetrical porphyrins C31.5a – c or C31.5d – e stabilized by either hydrogen bonding between the enaminoketone fragments or by coordination of nickel(II). 624 …”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“…15−17 The addition of alkyl chains to phenyl-substituted porphyrins has assisted in the on-surface construction of porphyrin dimers and nanoribbons. 18,19 Peripherally alkylated copper(II) octaalkoxyl-substituted phthalocyanine also form stable SAMs, which is attributed to the higher desorption barrier produced by the alkyl substituents. 20 A series of alkyloxyphenyl-substituted porphyrins were studied by Wang et al, and they found "high stability and close-packed assembly is attributed to van der Waals interactions between the alkyl chains and the graphite substrate, which substantially increases the desorption barrier of the combined molecules".…”
Section: ■ Introductionmentioning
confidence: 99%
“…Representative examples include the following studies. Molecular species such as n -alkylcyano­biphenyl (nCB), porphyrins, and phthalocyanines designed with long alkyl substituents (typically more than eight CH 2 groups), which have little effect on their electronic properties, produce well-defined SAMs on conducting surfaces under ambient conditions. The addition of alkyl chains to phenyl-substituted porphyrins has assisted in the on-surface construction of porphyrin dimers and nanoribbons. , Peripherally alkylated copper­(II) octaalkoxyl-substituted phthalocyanine also form stable SAMs, which is attributed to the higher desorption barrier produced by the alkyl substituents . A series of alkyloxyphenyl-substituted porphyrins were studied by Wang et al, and they found “high stability and close-packed assembly is attributed to van der Waals interactions between the alkyl chains and the graphite substrate, which substantially increases the desorption barrier of the combined molecules” .…”
Section: Introductionmentioning
confidence: 99%
“…Intrigued by the cooperative reactivity of manganese porphyrins adsorbed at adjacent locations at the solid–liquid interface, we decided to design and synthesize covalently connected metal-porphyrins, with the ultimate aim to investigate with STM the possible cooperativity between two metal centers in the same molecule. Several examples of covalently linked porphyrin dimers have been described [28,29,30,31,32] and some have been imaged with STM in an ultra-high vacuum environment or at a solid–liquid interface [33,34,35,36,37]. Our intention to adsorb porphyrin dimers as immobilized assemblies at a solid–liquid interface required the attachment of long aliphatic chains, which are known to aid assembly as a result of van der Waals interactions with the surface and intermolecular alkane chain interdigitation [38].…”
Section: Introductionmentioning
confidence: 99%